Possibilities of music therapy with children and families - Tuomi, Kirsi (2022)
The intention of this dissertation is to provide a comprehensive overview of early childhood music therapy and family centered practice, conceptualize the fields and to increase understanding on how the actual work is done and the phenomena experienced. The first substudy examines music therapy literature from 1990 to 2012 focusing on children aged 0 to 5 years old. 125 texts fulfilled the criteria of inclusion including a large variety of clinical descriptions and research papers. Historically the dominance from individual work has been shifting to dyadic/family work. The active methods most commonly utilized were singing and playing with instruments. Children with autism spectrum disorder (ASD) were most strongly represented together with paediatric patients and children with developmental disabilities. Interaction between family members and the positive factors were emphasized. The importance of fun and enjoyment was underlined throughout all client groups. (Tuomi et al., 2017.) The second substudy is an international survey study. A total of 125 responses were analysed. Participants’ responses indicated that music therapy with families is well established as an important field of practice that includes a large range of populations across the life span. Music therapists working with families emphasize that the work is holistic and flexible, both in terms of the theoretical approaches that inform their work and the methods/techniques that are included in sessions. The participants in this study advocated for more continuing professional development opportunities to further deepen and develop their practice. (Tuomi et al., 2021.) The aim of the third substudy was to gain deeper understanding on how foster parents reflect the different meanings of the Nurture and play (NaP) for foster families - intervention aimed for children aged one to five years of age. A stimulated recall method was chosen to correspond to these research targets. The parents´ reflections were evidently focused on the child, the importance of safety and the meaning of change during the process. Emotional qualities concerning both the child and the adult were emphasized. The foster parents were able to utilize their reflections within a wider context of place, relationships, and time. The results of the study and the core concepts of attachment theory are strongly related to each other. (Tuomi & Ala-Ruona, 2022.) The dissertation and its outcomes offer suggested priorities and suggestions for future research including the need for more specific and deep probing information, different perspectives, and emphasis on focus.